Shareholder actions - Charman, Andrew (Barrister); Du Toit, Johan (Barrister) (Bloomsbury, 2017)
"Shareholder Actions is a comprehensive guide to the possible actions shareholders may be entitled to pursue, on whichever side of the dispute they might be involved. As well as unfair prejudice and derivative actions, and the many personal actions arising from the Companies Act 2006, the book covers actions based in common law and equity, as well as actions based in other statutory law. It also explores occurrences of directors owing fiduciary duties directly to shareholders and the 'no reflective loss' rule providing a clear view of its scope and its limitations. The book refers to judgments in other related jurisdictions when it is necessary to substantiate a submission not already fully and authoritatively addressed by English law. Scottish cases are referred to where the House of Lords or Supreme Court have dealt with an issue, or where the point of law overlaps with English law. There are separate chapters on taxation issues, shareholder claims in Australia, due the large cross pollination between English and Australian law and, for comparative purposes, on Canada where a very different approach is taken with its common law based system."--Bloomsbury Publishing